LEAN-TECHNOLOGIES AS A RESOURCE OF EDUCATION MODERNIZATION - A. R. Groshev; G. E. Karataeva (Moscow Polytechnic University, 2018)
The article examines domestic practices of reducing losses in educational organizations. Attention has been paid to the activities of educational organizations aimed at reducing losses, both in the main production processes, and in the auxiliary processes that consume resources, but do not create value for consumers. This article is an attempt to estimate of the state of implementation of lean-technologies in the main production processes in higher education. There are references to not numerous examples of their use. Practical applications of lean technologies in auxiliary processes have been viewed in more detail. Based on the analysis of the information on the official site of public procurement, the authors consider a tendency to transfer the functions of accounting, personnel and legal support for outsourcing by state (municipal) agencies and departments, in particular they view the Moscow Region Government practice of outsourcing the auxiliary processes of subordinate educational organizations. The comparative analysis of costs per student has confirmed the effectiveness of outsourcing. The article dwells on the unique practice of Bauman Moscow State Technical University on the implementation of labor standards system.